EFFECT OF MICROSTRUCTURE AND RELATIVE HUMIDITY ON ATMOSPHERIC PITTING CORROSION OF DUPLEX STAINLESS STEEL BENEATH MGCL2 DROPS - Ali, Safa A.; Mohammed Ali, Haval B. (Science Journal of University of Zakho, 2023)
One of the main issues for intermediate-level nuclear waste (ILW) is atmospheric corrosion in stainless steel. The impact of microstructure on the pit shapes on three orientations of the duplex stainless steel DSS 2205 plate and the relative humidity impact on the atmospheric corrosion pits of DSS beneath MgCl2 drops is determined through the use of four characterization tools: X-ray diffraction (XRD), Energy dispersive X-ray (EDX) analyses, Scanning electron microscopy (SEM), and optical microscopy. The pits on the top surface (LT) appears layered like an attack and mostly hemispherical, while the long transverse (LS) and short transverse (ST) planes reveal elongated strings. The map scan of EDX indicates mixed oxide inclusions and MnS inclusion existing in the steel alloy and the XRD analyses present the existence of two-phase both austenite γ and ferrite α peaks. The pit shape and area were influenced by relative humidity (RH) change. At RH 35% the trend of pits in 1-week exposure revealed a larger area of pit mouth than in RH 45%. For the same exposure time and in both RHs, the area seemed to be greater at the droplet’s center than in the edge of the droplet.